WOMEN AS A STRATEGIC GROUP: WOMEN'S STRATEGY IN POLITICAL NETWORKS THROUGH THE ECONOMIC AREA: (IWAPI NTB CASE STUDY) - Safitri, Purnami; Trisno Aji, Wahyu; Adabiyah, Radiyatun; Harani, Faizah (UIN Mataram, 2024)
Abstract Women’s participation in economic field and politic is often viewed in a dichotomous manner, where the economy is referred as